Cultivating marine bacteria under laboratory conditions: Overcoming the “unculturable” dogma - Rodrigues, Carlos J. C.; de Carvalho, Carla C. C. R. (Frontiers in Bioengineering and Biotechnology, 2022)
Underexplored seawater environments may contain biological resources with potential for new biotechnological applications. Metagenomic techniques revolutionized the study of bacterial communities but culture dependent methods will still be important to help the biodiscovery of new products and enzymes from marine bacteria. In this context, we promoted the growth of bacteria from a marine rock pond by culture dependent techniques and compared the results with culture independent methods. The total number of bacteria and diversity were studied in different agar plate media during six weeks. Agar plate counting was of the same order of magnitude of direct microscopy counts. The highest efficiency of cultivation was 45% attained in marine agar medium. Molecular analysis revealed 10 different phyla of which only 4 were isolated by the culture dependent method. On the other hand, 4 taxonomic orders were detected by cultivation but not by the molecular technique. These include bacteria from the phyla Bacillota and Actinomycetota. Our study shows that it is possible to grow more than the traditionally considered 1% of bacteria from a seawater sample using standard agar plate techniques and laboratorial conditions. The results also demonstrate the importance of culture methods to grow bacteria not detected by molecular approaches for future biotechnological applications.